Goofy's hat - Ring, Susan (New York : Disney Press, 2008)
Where is Goofy's hat? Mickey and his friends look everywhere for it. They search high and low, near and far. You'll be suprised where Goofy finally finds his hat.
Keywords: Loose -- Fiction